The effects of melatonin and prostaglandin E1 analogue on experimental hepatic ischaemia reperfusion damage - Bülbüller, N; Çetinkaya, Z; Akkus, MA; Çifter, Ç; Ilhan, YS; Dogru, O; Genç, K (Blackwell Publishing Ltd, 2003)
The effects of antioxidant melatonin and a prostaglandin E-1 analogue (PGE(1)) on hepatic ischaemia reperfusion damage were investigated. Fifty rats were divided into five equal groups: sham, control, melatonin, PGE(1) and combined treatment. No procedures were applied to the sham group. In the control and treatment groups, the hepatic hilus was clamped at the level of the hepatic artery and portal vein for 60 min and reperfusion was provided for two hours. In the treatment and combined treatment groups, melatonin was administered intramuscularly at a dose of 20 mg/kg 15 mins before reperfusion, and PGE(1) was administered intravenously at a dose of 25 mg/kg 1 min before reperfusion. Blood samples for SGOT, SGPT GSH-Px, SOD and MDA measurements and hepatic tissue samples were taken. The decrease in the plasma MDA levels was statistically significant in the melatonin and combined treatment groups, but not in the PGE(1) group (p > 0.025). A significant decrease was found in the tissue IVIDA levels of the treatment groups (p < 0.025). The decrease in SGOT and SGPT levels in the PGE(1) group was significant (p < 0.025), but the decreases in the melatonin and combined treatment groups were not significant (p > 0.025). Melatonin and PGE(1) were found to be effective in reducing the hepatic ischaemia reperfusion damage in rats. However, the damage could not be reversed. Combined treatment was found not to be superior to melatonin or PGE(1) alone.
Keywords: Free-Radicals; Liver; Injury; Assay; Serum; Rats